Diabetic muscle infarction: A case report - C Levine Emma; K Brennan Sara; P Johnston Gregory; P Gilbert Matthew (Journal of Family Medicine and Primary Care)
Diabetes muscle infarction (DMI) is a rare complication of diabetes in which patients who present with DMI more commonly have some form of kidney disease in addition to diabetes mellitus. DMI typically presents with muscle pain and swelling. Diagnosis typically requires imaging (MRI with gadolinium contrast is the gold standard) and a variety of laboratory studies may aid in the diagnosis. Treatment of DMI varies depending on the severity of the case. In general patients recover quickly, though there is a risk of recurrence. This particular case report is a 36 year old female who presented with right lower extremity pain and chronic kidney disease. Case reports like this are important to highlight DMI as it is likely to become more common as diabetes continues to become more prevalent.